Rural Staffing in the Health Sector: Attraction and Retention Options For Uganda - Namugoji, Esther (SPEED Initiative, 2019)
Uganda is committed to universal health coverage and promoting the wellbeing for all its citizens at all ages, as per Goal 3 of the UN Sustainable Development Goals. This commitment includes the challenge to end the epidemics of HIV/AIDS, malaria, tuberculosis and non-communicable diseases. According to the 2016 Uganda Demographic and Health Survey (UDHS), the country’s maternal, infant and child mortality rates remain among the highest globally. Maternal mortality is at 336 deaths for every 100,000 live births, while infant mortality is at 43 deaths per 1,000 live births1. Although the UDHS also shows that more women are giving birth in health facilities and receiving antenatal and postnatal care, rural areas still lag behind urban areas on all these indicators.